The Power Mean Inequality is a classical result that compares the arithmetic mean ( f A M ), the geometric mean ( f G M ), the quadratic mean ( f Q M ) and the harmonic mean ( f H M ) of a list of positive numbers :
f Q M ≥ f A M ≥ f G M ≥ f H M
Let's define the trigonometric mean of two positive real numbers x , y such that x y > 1 as :
f T M ( x , y ) = − g ( x , y ) 1 + 1 + g 2 ( x , y ) where : g ( x , y ) = tan ( tan − 1 ( x ) + tan − 1 ( y ) )
What is the generalization of the Power Mean Inequality on x , y that would include the trigonometric mean ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did same here but it was really a long process.
Wow, looks like a scary process...
Log in to reply
Ya,But once started the flow then it is just the maths.
Well actially if you are a genius problem solver you can solve this really quickly without solving it mathematically. You just go by pin-pointing by similarity, out of possible answers formulated as abcde abdce adcbe abdec adcbe you have most primary similarities three, then you cut of from there ABdec, ABcde, ABdce and you eliminate by separating secondary similarities Dec and Dce, then because there is only two and only a switch between terms you don't have anymore to separate so you use an algorithm by noticing in the previous answers which term is most interchanged and never repeats or mrepeats less than the other comparative term (E) on the same spot for instance if C never repeats on the same spot and always interchanges it will be Ce, but if both C and E repeat on same locations you just count which one repeats on less locations over the ratio of those groups entering primary, secondary phases.
Problem Loading...
Note Loading...
Set Loading...
Using the tangent addition formula, g ( x , y ) = tan ( tan − 1 ( x ) + tan − 1 ( y ) ) = 1 − tan ( tan − 1 ( x ) ) tan ( tan − 1 ( y ) ) tan ( tan − 1 ( x ) ) + tan ( tan − 1 ( y ) ) = 1 − x y x + y .
Therefore, f T M ( x , y ) = − g ( x , y ) 1 + 1 + g 2 ( x , y ) = − 1 − x y x + y 1 + 1 + ( 1 − x y x + y ) 2 which simplifies to f T M ( x , y ) = x + y x y − 1 + x 2 y 2 + x 2 + y 2 + 1 .
Now f Q M ≥ f G M , so for two positive real numbers x and y , 2 x 2 + y 2 ≥ x y . Then if x y > 1 ,
2 x 2 + y 2 ≥ x y
2 x 2 + y 2 ≥ x y
x 2 + y 2 ≥ 2 x y
x 2 y 2 + x 2 + y 2 + 1 ≥ x 2 y 2 + 2 x y + 1
x 2 y 2 + x 2 + y 2 + 1 ≥ ( x y + 1 ) 2
x 2 y 2 + x 2 + y 2 + 1 ≥ x y + 1
x y + x 2 y 2 + x 2 + y 2 + 1 ≥ 2 x y + 1
x y − 1 + x 2 y 2 + x 2 + y 2 + 1 ≥ 2 x y
x + y x y − 1 + x 2 y 2 + x 2 + y 2 + 1 ≥ x + y 2 x y
x + y x y − 1 + x 2 y 2 + x 2 + y 2 + 1 ≥ x 1 + y 1 2
f T M ≥ f H M
Also, f A M ≥ f G M , so for two positive real numbers x and y , 2 x + y ≥ x y . Then if x y > 1 ,
2 x + y ≥ x y
x + y ≥ 2 x y
( x + y ) ( x y − 1 ) ≥ 2 x y ( x y − 1 )
x y ( x + y ) − ( x + y ) ≥ 2 x y x y − 2 x y
x y ( x + y ) ( x + y ) − ( x + y ) ( x + y ) ≥ 2 x y x y ( x + y ) − 2 x y ( x + y )
x y ( x + y ) 2 − ( x + y ) 2 ≥ 2 x y x y ( x + y ) − 2 x y ( x + y )
x y ( x + y ) 2 − 2 x y x y ( x + y ) + 2 x y ( x + y ) ≥ ( x + y ) 2
x y ( x 2 + 2 x y + y 2 − 2 x x y − 2 y x y ) + 2 x y ( x + y ) ≥ x 2 + 2 x y + y 2
x y ( x 2 + 2 x y + y 2 − 2 x x y − 2 y x y ) + 2 x y ( x + y ) − 2 x y ≥ x 2 + y 2
x y ( x 2 + 2 x y + y 2 − 2 x x y − 2 y x y ) + 2 x y ( x + y ) − 2 x y x y ≥ x 2 + y 2
x y ( x 2 + 2 x y + y 2 − 2 x x y − 2 y x y ) + 2 x y ( x + y − x y ) ≥ x 2 + y 2
x 2 y 2 + x y ( x 2 + 2 x y + y 2 − 2 x x y − 2 y x y ) + 2 x y ( x + y − x y ) + 1 ≥ x 2 y 2 + x 2 + y 2 + 1
x y ( x 2 + 3 x y + y 2 − 2 x x y − 2 y x y ) + 2 x y ( x + y − x y ) + 1 ≥ x 2 y 2 + x 2 + y 2 + 1
x y ( x + y − x y ) 2 + 2 x y ( x + y − x y ) + 1 ≥ x 2 y 2 + x 2 + y 2 + 1
( x y ( x + y − x y ) + 1 ) 2 ≥ x 2 y 2 + x 2 + y 2 + 1
x y ( x + y − x y ) + 1 ≥ x 2 y 2 + x 2 + y 2 + 1
x y ( x + y ) − x y + 1 ≥ x 2 y 2 + x 2 + y 2 + 1
x y ( x + y ) ≥ x y − 1 + x 2 y 2 + x 2 + y 2 + 1
x y ≥ x + y x y − 1 + x 2 y 2 + x 2 + y 2 + 1
f G M ≥ f T M
Since f G M ≥ f T M and f T M ≥ f H M , and f Q M ≥ f A M ≥ f G M ≥ f H M , f Q M ≥ f A M ≥ f G M ≥ f T M ≥ f H M .